Preface: Hydrological Sciences in the Anthropocene – a structured community effort - Cudennec, Christophe; Amoussou, Ernest; Cavus, Yonca; Chaffe, Pedro L B; Fischer, Svenja; Grimaldi, Salvatore; Kileshye Onema, Jean-Marie; Merheb, Mohammad; Polo, Maria-Jose; Servat, Eric; Volpi, Elena (Proceedings of the International Association of Hydrological Sciences, 2025)
The International Association of Hydrological Sciences (IAHS) celebrated its centennial in 2022 during the 11th Scientific Assembly held over 29 May–3 June in Montpellier(France); and is celebrating in 2024 a century of publications. This volume materializes the proceedings of the 2022 Assembly and marks the anniversary of the long-term publi cation dynamics, with articles tackling very actual problems and questions, from across many countries of the World. The International Association of Hydrological Sciences/Association Internationale des Sciences Hydrologiques (IAHS) was created in 1922 in Rome (Italy) in the form of the International Section of Scientific Hydrology/Section Internationale d’Hydrologie Scientifique of the International Union of Geodesy and Geophysics/Union Internationale de Géodésique et Géophysique (IUGG), itself member of the International Research Council/Conseil International de Recherches both created in 1919 in Brussels (Belgium) (Nature, 1928; Schroeder-Gudehus, 2014, Ismail zadeh and Joselyn, 2019) (Names in French language are kept here as it was the language used for the proceedings at the time). The IAHS developed over a century as described by osbjerg and Rodda (2019), alongside the parent IUGG (Joselyn and Ismail-Zadeh, 2019; Joselyn et al., 2019) and sister learned societies (including the emergence in 2007 of the international Association of Cryospheric Sciences (IACS); Allison et al., 2019) and with strong partnerships in the United Nations system, in particular with UNESCO IHP and WMO (see e.g. Young et al., 2015a, b; Dixon et al., 2022). The records of the first plenary meeting of the Section in 1924 shaped the first volume of the Section’s bulletin (Sec-tion Internationale d’Hydrologie Scientifique, 1924), which then became the Red Book series in 1951 with volume 32 (where the red colour was first used to highlight the cover)